Permission in some selected plays - Al-Aadili, Nesaem Mehdi (Advances in Social Sciences Research Journal, 2019)
This study deals with the speech act of permission as one of the various functions performed through the use of language. It is an attempt to investigate permission, which can be asked or given, depending on the authority of the hearer. To present and discuss the speech act of permission and its types, the study focuses on its pragmatic and syntactic aspects. Moreover, the study deals with the analysis of permission in three English dramatic texts including: "Flowering Cherry" and "A Man for all Seasons" by Robert Bolt, and "You Never Can Tell" by Bernard Shaw.